American Evangelicals and Islam: Their Perspectives, Attitudes and Practices Towards Muslims in the US. (January 2017) - Bhatia, Amit A
In light of the increasing presence of Muslims in the US, this article elucidates the perspectives, attitudes and practices of American evangelicals towards Muslims in the US. The discussion is informed by data that were gathered through a qualitative study of 40 lay American evangelicals and four pastors, as well as through a focus group study of an evangelical outreach ministry among Muslims. Literature on religious diversity in the US forms the background within which the information drawn from the qualitative interviews and focus group study is discussed and analyzed. The respondents' perspectives and attitudes towards Islam and Muslims in general are quite negative, as well as conflicted in that while the respondents claimed to be open to interacting and dialoguing with Muslims, their practices towards Muslims were often not so hospitable. This inhospitality was a result of a general fear of Islam and Muslims exhibited by the respondents.